1999
DOI: 10.1098/rspb.1999.0623
|View full text |Cite
|
Sign up to set email alerts
|

An apparent excess of sex– and reproduction–related genes on the human X chromosome

Abstract: We describe here the results of a search of Mendelian inheritance in man, GENDIAG and other sources which suggest that, in comparison with autosomes 1, 2, 3, 4 and 11, the X chromosome may contain a significantly higher number of sex- and reproduction-related (SRR) genes. A similar comparison between X-linked entries and a subset of randomly chosen entries from the remaining autosomes also indicates an excess of genes on the X chromosome with one or more mutations affecting sex determination (e.g. DAX1), sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
109
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 40 publications
3
109
0
1
Order By: Relevance
“…The accumulation of both male-and female-biased genes on the X chromosome is consistent with the predictions of W. Rice 3 and previous reports on mice and humans [6][7][8] . We believe that the paucity of testis-enriched genes on the mouse X is mainly attributable to the effects of MSCI 19,20 .…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The accumulation of both male-and female-biased genes on the X chromosome is consistent with the predictions of W. Rice 3 and previous reports on mice and humans [6][7][8] . We believe that the paucity of testis-enriched genes on the mouse X is mainly attributable to the effects of MSCI 19,20 .…”
supporting
confidence: 91%
“…One model predicts that genes with sexbiased expression should be enriched on the X chromosome [2][3][4][5] . In agreement with Rice's hypothesis 3 , spermatogonial genes are over-represented on the X chromosome of mice 6 and sex-and reproduction-related genes are over-represented on the human X chromosome 7,8 . Male-biased genes are under-represented on the X chromosome in worms and flies [9][10][11] , however.…”
supporting
confidence: 86%
“…A large body of literature suggests that the influence of X-linked genes should be greater on sexually selected (often sex-limited) traits than autosomal genes, and in some studies this has been the case (Reinhold, 1998;Hurst and Randerson, 1999;Saifi and Chandra, 1999). When sexual selection favors trait expression in hemizygous males, but not in females, X-linked loci evolve more quickly (Rice, 1984;Charlesworth et al, 1987) and are more likely to persist than autosomal loci (Reinhold, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The human X encodes a mixture of widely expressed housekeeping genes, as well as genes that have specialized functions such as visual pigments and blood clotting factors. However, there is an elevated frequency (compared with the autosomes) of genes with sex and reproduction-related functions (Saifi and Chandra, 1999). It was suggested that the accumulation of male advantage genes on the human X chromosome is the result of rapid selection in the hemizygous male (Rice, 1987).…”
Section: Eutherian Sex Chromosomesmentioning
confidence: 99%